A Review of Recent Curcumin Analogues and Their Antioxidant, Anti-Inflammatory, and Anticancer Activities - Kirandeep Kaur; Ahmad K. Al-Khazaleh; Deep Jyoti Bhuyan; Feng Li; Chun Guang Li (MDPI AG, 2024)
Curcumin, as the main active component of turmeric (Curcuma longa), has been demonstrated with various bioactivities. However, its potential therapeutic applications are hindered by challenges such as poor solubility and bioavailability, rapid metabolism, and pan-assay interference properties. Recent advancements have aimed to overcome these limitations by developing novel curcumin analogues and modifications. This brief review critically assesses recent studies on synthesising different curcumin analogues, including metal complexes, nano particulates, and other curcumin derivatives, focused on the antioxidant, anti-inflammatory, and anticancer effects of curcumin and its modified analogues. Exploring innovative curcumin derivatives offers promising strategies to address the challenges associated with its bioavailability and efficacy and valuable insights for future research directions.